Entre a história e a memória: uma análie discursiva do documentário sobreviventes do holocausto - Krümmel, Elivélton Assis (2019)
The present study, entitled “Between history and memory: a discursive analysis of the documentary Survivors of the Holocaust”, aims to carry out a discursive analysis of a documentary that presents testimonials of survivors of the holocaust, so that it is possible to work with the notion of memory and its different functions, explaining the space of the testimony inside the documentary, for reflect without how the subject discursiviza and symbolizes the event. In view thereof, we worked with countless cuts, understood as discursive units (ORLANDI, 1984), which were selected from the documentary produced by Steven Spielberg in 1993, which we chose as the object of analysis. As well, this study, anchored in the presuppositions of Discourse Analysis (DA), represents a possibility of looking at the past, to mean it from the discourse of the witness, as a survivor of the Holocaust and thus understand the language functioning, producing meanings, as symbolic work that is based on the general social work, constituted by man and history (ORLANDI, 2009). The past that can be forgotten or preserved (ROBIN, 2016). A work, therefore, based on yet another of the many versions of the event. An effect. From this, we organize our work in three parts: in the first part, “From reality to fiction, from the visible to the audible: a look at the documentary”, we discuss the workings of the documentary in the Discourse Analysis (DA) to introduce a possibility of mobilizing the theoretical device and the analytical device used in this research; in the second part, “Between history and memory: a constant transit”, we discuss the main historical facts that contemplate the establishment of the Nazi Regime in Germany, in 1933 until 1945, a course that bases our reflections, mainly in what concerns the importance of the testimony, and the narrate of history, that is, the relations between language, subject and history, whose interlinkages are constitutive of the old/elderly subject, producing possible meanings; and the third part, “We lowered the voices, we put out the candles... And we saw that it was the beginning of hell”, corresponds to the analyzes undertaken, organized into nine blocks of countless cuts, sequenced under the aegis of the passage of time (from the establishment of the Nazi Regime to its decline), a space in which we reflect on how an imaginary on the Holocaust which, in its conjuncture, reveals important aspects of the relationship of the old/elderly subject with this memory and with certain symbolic objects. It is also worth noting that work is a gesture of interpretation (ORLANDI, 2009), a view that, in the face of materiality, produces effects of meaning through the constant transit between history and memory: a possible path through the thread of testimonial discourse in which the old/elderly subject, in the condition of survivor of the Holocaust, is capable of supporting the symbolic, which is fully functioning, leaning to lack, failure, and saturation.